Comparing Layer 1 and Layer 3 Relay Stations Deployment in a LTE Network - Martins, André (2013)
The relay solution in planning of mobile networks, has the aim of increasing the network coverage and/or capacity. According to the open literature, this technique will be highly used in the next Long Term Evolution (LTE) Networks. The Relay Station (RS) performance varies with its position in the cell, with the radio conditions to which RSs and User Equipments (UEs) are subjected and with the RS capacity to receive, process and forward the information. The aim of this paper is to compare the performance of the Layer 1 (L1) and Layer 3 (L3) RS types, and to determine the ideal position in which a RS should be placed, with the aim of maximizing the UE throughput.